Semiotic Analysis of Da'wah Message About Morals in The Short Film Ji Dullah - Imani, Ahmad Yazid (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2024)
This research is motivated by the social criticism conveyed in the short film